(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
The Government of Republic of North Macedonia has made a commitment to care and education for children with developmental delays by signing the Convention on the Rights of the Child. Nevertheless, early intervention centres in North Macedonia cannot always meet the preconditions and ease access and care for children with developmental disabilities or delays. In the U.S. services for young children, from birth to the 3rd birthday are called Early Intervention (EI) or Part C services. Once the child turns three (and until 21), educational services are provided under Part B of IDEA. EI focuses on family-centred services, individually planned educational programs, and specialized teaching approaches. The primary aim of the research was to explore the EI system in the States as well as the implementation of policy into practice. The secondary goal was related to identifying positive practices and policies that can be applied in an international context. A qualitative study research methodology was used with a non-rigid and naturalistic design. Qualitative content analysis was the research tool. This paper contains a qualitative review of papers in the following areas: Historical trends in EI; Current trends in EI; Models of service delivery; Transdisciplinary EI approach; and Coaching of families within EI.